Manajemen Kurikulum Dalam Penerapan Proyek Penguatan Profil Pancasila (P5) di Madrasah Aliyah Negeri 2 Probolinggo - Haqqi, Izzul; Arisanti, Kustiana; Komar, Abdul (El-Idare, 2024)
This research aims to explain the role of curriculum management in the implementation of the Strengthening Pancasila Profile (P5) project with a case study at Madrasah Aliyah Negeri (MAN) 2 Probolinggo. P5 is an initiative that aims to strengthen the understanding and implementation of Pancasila values in the educational environment. MAN 2 Probolinggo was chosen as the research location because it is one of the educational institutions that runs the P5 project with high commitment. This study used a qualitative approach with data collection techniques through in-depth interviews, participatory observation, and document analysis. The respondents consisted of principals, teachers and management staff who were directly involved in the implementation of the P5 project. The collected data were analyzed using content analysis techniques to identify the role of curriculum management in supporting the P5 project. The results showed that curriculum management has a significant role in the successful implementation of the P5 project at MAN 2 Probolinggo. The practical implication of this study is the importance of the active role of curriculum management in supporting efforts to improve the understanding and application of Pancasila values in schools. The findings of this study are expected to be an input for education policy makers to strengthen the role and function of curriculum management in supporting the goals of character education in Indonesia.